The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1161/circulationaha.117.031984
|View full text |Cite
|
Sign up to set email alerts
|

ICare-ACS (Improving Care Processes for Patients With Suspected Acute Coronary Syndrome)

Abstract: Background: Efforts to safely reduce length of stay for emergency department patients with symptoms suggestive of acute coronary syndrome (ACS) have had mixed success. Few system-wide efforts affecting multiple hospital emergency departments have ever been evaluated. We evaluated the effectiveness of a nationwide implementation of clinical pathways for potential ACS in disparate hospitals. Methods: This was a multicenter pragmatic stepped-wedge before-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 25 publications
(29 reference statements)
5
33
0
4
Order By: Relevance
“…Many studies have been published using an accelerated diagnostic protocol strategy in the management of ED suspected ACS patients. [20][21][22][23] These generally use risks scores (e.g., EDACS, HEART), ECG, and serial troponin obtained at baseline and 1, 2, or 3 hours. What is clear is that, as the sensitivity of the clinically available assays have improved, so have safe ED discharge rates as evaluated by 30-day outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been published using an accelerated diagnostic protocol strategy in the management of ED suspected ACS patients. [20][21][22][23] These generally use risks scores (e.g., EDACS, HEART), ECG, and serial troponin obtained at baseline and 1, 2, or 3 hours. What is clear is that, as the sensitivity of the clinically available assays have improved, so have safe ED discharge rates as evaluated by 30-day outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that hypoalbuminemia (<3.5 g/dL) and a low baseline hemoglobin level were independent predictors of long‐term outcomes for patients with myocardial infarction after PCI (Akirov et al, ; Hosseini et al, ; Wada et al, ). Most patients with ACS after PCI were hospitalized for no more than 3 days, as the critical process for ACS management was applied to them in general (Than et al, ). Our findings showed that discharging patients with ACS within 1–3 days was related to a low incidence of MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that discharging patients with ACS within 1–3 days was related to a low incidence of MACE. Although LOS must be carefully balanced with healthcare quality, it is a critical index of healthcare efficiency regarding inpatient guideline adherence for patients with ACS (Swaminathan et al, ; Than et al, ; Tickoo et al, ). Despite these findings, our results obtained through multi‐variate Cox regression analysis demonstrated that the frequency of nursing activities was the strongest factor affecting the incidence of MACE in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OR-based studies addressing long LOS are evidenced in Chan et al [91], Derni et al [87], Liu et al [95], and Oueida et al [86,96]. Apart from the aforementioned single techniques, less popular methods like critical pathways [88,89,97], pivot nursing [92], and process redesign [94] were also used by some practitioners and researchers to diminish the total burden produced by long ED-LOS. Table 3 presents all the papers aiming at shortening the door-to-physician time in EDs.…”
Section: Papers Focusing On Reducing the Extended Losmentioning
confidence: 99%